Hubungan Brand Image Dengan Kepuasan Konsumen Parfum Azzwars di Kota Padang - Naldi, Remon; Rahma Nio, Suci (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The relationship of brand image with consumer satisfaction azzwars perfume. The research aims to look at the relationship between brand image and consumer satisfaction of azzwars perfume in the city of Padang. This research uses quantitative methods and the research design used is quantitative correlational. The research population is the community in the city of Padang. The sampling technique uses purposive sampling technique. This study uses a brand image scale and customer satisfaction consisting of aspects according to Aaker & Biel and Kotler. The data analysis technique used is the product moment correlation from Karl Pearson. The results of this study found a correlation coefficient (r) of 0.265 and p = 0.040 (p <0.05) which showed a significant relationship between brand image and consumer satisfaction of azzwars perfume in Padang City